2016
DOI: 10.1186/s13362-016-0031-7
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical assessment of drug build-up in the posterior eye following transscleral delivery

Abstract: Delivery of drugs to the posterior segment of the eye is a significant challenge in the field of opthalmic pharmaceuticals. Several restrictive barriers hinder drug delivery to this district. Static barriers include tissues and limiting membranes, while dynamic barriers include drug clearance mechanism from blood and lymphatics. Strategies for delivering drugs to the posterior segment most often consist in topical ocular medications or systemic administrations, but dose/response profiles are generally very poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The prediction of drug distribution within the eye to avoid tissue toxicity and to determine the precise drug levels in target tissues has been a subject of modeling studies. Computational methods have been described to model drug transport following intravitreal injection from a point source [22,23,24,25,26,27] and other models have been developed to simulate drug distribution by an intraocular or periocular implant [25,28,29]. Early models primarily considered diffusion, while more recent models consider both diffusion and convection produced by the aqueous humor flow.…”
Section: Introductionmentioning
confidence: 99%
“…The prediction of drug distribution within the eye to avoid tissue toxicity and to determine the precise drug levels in target tissues has been a subject of modeling studies. Computational methods have been described to model drug transport following intravitreal injection from a point source [22,23,24,25,26,27] and other models have been developed to simulate drug distribution by an intraocular or periocular implant [25,28,29]. Early models primarily considered diffusion, while more recent models consider both diffusion and convection produced by the aqueous humor flow.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the contribution of RPE pumping always appear important, especially when the retina is the therapeutic target. The RPE pumping effect, included in a very limited selection of papers, is modeled as a fictitious advective field or through different inward/outward permeabilities of the RPE membrane [13,19,20]. The inclusion of the significant clearance pathways for a certain drug administration mode is rather varied.…”
Section: Geometrical Modelingmentioning
confidence: 99%
“…Choriocapillaries are often treated as a perfect sink [16,21] or they are modeled via porous jump equations [13]. Retinal blood vessels are only considered in [18] and, via a mixture equation approach, in [20]. Generally, the fluid filtration is assumed to be steady state (except for) [15] and not influenced by the drug transport.…”
Section: Geometrical Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Various research with computational modelling has been reported to model drug transport following intravitreal injection. 323,327,[337][338][339][340] Others have reported the effect of drug distribution from intraocular or periocular implant 329,338,341 and for the development of IVIVCs. 342,343 Most studies describe the distribution of injected materials in the vitreous both theoretically and experimentally, but there has been much less described to correlate with real-time data on the distribution and elimination of drugs released from implants or ocular formulations.…”
Section: Drug Distribution After Intravitreal Injectionmentioning
confidence: 99%